(untitled) (PAAN Journal, 2026)
This study investigates the structural challenges and reform needs of Nepal’s public pension system, with a particular focus on government schoolteachers. Drawing on pensioner data from fiscal year 2011–12 to 2023–24, the study identifies a sharp increase in the number of retirees, with the teaching sector exhibiting the highest average annual growth rate among all public sectors. This trend is closely linked to rising life expectancy, which correlates strongly (R=0.8568) with the growing number of pensioners. The delayed and uneven implementation of the contribution-based Pension Fund Act, 2075, has created legal ambiguity, especially for transitional appointees, and contributed to administrative inefficiencies and inter-agency coordination gaps. The lack of actuarial valuation further impedes evidence-based pension planning. In response, the study proposes a Mixed Pension Scheme that preserves non-contributory benefits for legacy teachers while introducing a contributory model for new entrants. Comparative analysis of SAARC countries, including India, Bangladesh, Bhutan, and Pakistan, supports the feasibility of phased, multi-pillar reforms. The study recommends regular actuarial assessments and designates the Employees Provident Fund as the most capable institution to manage teacher pensions, due to its administrative experience and financial credibility. The findings call for urgent, balanced reform to ensure sustainability, equity, and fiscal resilience.